Mediation analysis of mental health characteristics linking social needs to life satisfaction among immigrants - David Adzrago; Faustine Williams (Elsevier, 2023)
Background: Life satisfaction contributes to improved long and healthy lives, enhanced biological function, better mental health, and decreased mortality risks. Social needs (e.g., food security, employment, healthcare utilization) are important determinants of mental health and life satisfaction among immigrants. However, there is limited literature on how social needs influence mental health, which, in turn, affects life satisfaction among immigrants. We examined whether mental health influences the mechanisms of the relationship between social needs and life satisfaction among immigrants. Methods: We used the 2021 cross-sectional National Health Interview Survey data on U.S. immigrants (n = 4320) aged ≥18 years. We conducted weighted mediation analyses with multiple linear regression. Life satisfaction (scores 0-10; ≥1 as higher life satisfaction) was the dependent variable; independent variables were food security, employment, and healthcare utilization; and the mediator, serious psychological distress (SPD: scores 0-24; ≥1 as higher SPD). Results: The total effect (not accounting for SPD) of food insecurity (vs. secure) on life satisfaction was negative (β = −0.61, p < 0.001); the direct effect (after accounting for SPD) was not statistically significant (β = −0.21, p = 0.153), while the indirect effect (food insecurity's effect explained by SPD) was negative (β = −0.40, p < 0.001). The total (β = 0.32, p < 0.001), direct (β = 0.24, p = 0.004), and indirect (β = 0.09, p = 0.006) effects of being employed (vs. unemployed) on life satisfaction were positive. The total (β = −0.12, p = 0.116) and direct (β = −0.03, p = 0.683) effects of healthcare utilization within the past year (vs. more than a year) on life satisfaction were not statistically significant, whereas the indirect effect was negative (β = −0.09, p < 0.001). Conclusions: SPD mediates the effect of food security, healthcare utilization, and employment on life satisfaction, suggesting the need to improve social needs and mental health among immigrants.